Análisis de la infraestructura tecnológica en la transmisión de datos en medidores industriales de CNEL – EP Los Ríos - Coello Huilcapy, Jaime Alfredo (2019)
The case study with the topic Analysis of the technological infrastructure in the transmission of data in industrial meters of CNEL - EP Los Ríos, aims to determine the problem that is being presented in the use of technology based on the transmission of GPRS data , where, thanks to countless tools such as dynamic cellular coverage maps displayed on websites belonging to the mobile phone service distribution companies, they facilitate geographical identification where cell coverage levels are low, hence data transmission from points of measurement to the concentrator are not efficient, for this it is concluded that implementing whip or Marconi type antennas will overcome the problem